Hypohidrotic Ectodermal Dysplasia: Breastfeeding Complications Due to Impaired Breast Development - Wahlbuhl-Becker, Mandy; Faschingbauer, Florian; Beckmann, Matthias; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2017)
Background X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia, is caused by mutations in the gene EDA. While only affected men develop the full-blown clinical picture, females who are heterozygous for an EDA mutation often also show symptoms such as hypodontia, hypotrichosis and hypohidrosis. These women may also suffer from malformations of the mammary gland which represent not just a cosmetic problem but can limit their breastfeeding capability. This paper summarizes the findings of the first systematic study on the impact of hypohidrotic ectodermal dysplasia on breastfeeding. Patients Thirty-eight adult female members of the German-Swiss-Austrian ectodermal dysplasia patient support group participated in a structured interview; most of them also agreed to a photodocumentation of their mammary region. Thirty-one women carried mutations in EDA (Group A) and seven were affected by other forms of hypohidrotic ectodermal dysplasia (Group B). Results 39 % of the women of Group A reported that their breasts were of different size or entirely absent on one side. In Group B, 86 % of the women reported differently sized or even absent breasts; two of these women lacked both breasts entirely. Most women described their nipples as exceptionally flat. 10 % of the women of Group A had more than two nipples. The high percentage of deviations from the norm was confirmed in the photodocumentation. Both groups had few or no sebaceous glands of Montgomery in the areolar region. Around 80 % of interviewed women had children and had attempted to breastfeed their first child. 67 % of the mothers in Group A had had difficulty in breastfeeding their infants and generally attributed this difficulty to their flat nipples. All of the mothers in Group B reported difficulties in breastfeeding; 60 % had not been able to breastfeed their first child. Conclusion Mothers with hypohidrotic ectodermal dysplasia very often have difficulty in breastfeeding because of their impaired breast development. This causal relationship needs to be taken into account in lactation counseling.
EVALuna2:34219